A Computer-Based Surveillance System to Support Discharge Planning: An Implementation within a Hospital Information System - Crawford, A.G. (1988)
This paper describes an innovation designed to improve discharge planning and, potentially, reduce the length of inpatient stays. Unlike other approaches, this one has been implemented within a Hospital Information System. The rationale is that reports integrating clinical and non-clinical data gathered upon admission can enable the Social Work Manager to assign staff more effectively, i.e., to the most difficult cases, and can enable staff to perform discharge planning more effectively, i.e., more pro-actively. The paper reviews the use of computers in social work and provides a critique, not of the models proposed, but of the implementations attempted to date. We contend that our approach will prove more successful than those other implementations because ours is based on an integrated and almost totally-electronic medical record keeping system, encompassing observations by both clinical and non-clinical staff.